Food Security in South Asia: Issues and Opportunities - Surabhi Mittal; Deepti Sethi (Indian Council for Research on International Economic Relations (ICRIER), 2009)
Food security is defined as economic access to food along with food production and food availability. Agriculture in the SAR (South Asian Region) is caught in a low equilibrium trap with low productivity of staples, supply shortfalls, high prices, low returns to farmers and area diversification - all these factors can be a threat to food security. South Asia still has the highest number of people (423 millions) living on less than one dollar a day. The region has the highest concentration of undernourished (299 million) and poor people with about 40 per cent of the world's hungry. Despite an annual 1.7 per cent reduction in the prevalence of undernourishment in the region in the past decade, the failure to reduce the absolute number of the undernourished remains a major cause for concern. Estimates by the Food and Agricultural Organisation (FAO) indicate that by 2010, Asia will still account for about one-half of the world's undernourished population, of which two-thirds will be from South Asia. Though SAARC countries have established a food bank to meet the needs of food security in the region, it has not been operational even during times of crisis. This is despite the felt need of member nations to evolve mechanisms to make the SAARC Food Security Reserve operational. It is against this background that this study has been undertaken. Conducted in collaboration with think-tanks from South Asian countries, it aims to identify issues relating to food security, the policy initiatives taken to tackle these issues, evaluate these policies and suggest measures to overcome identified constraints in order to improve the food security situation in the region.
Keywords: Q18; O57; 330; South Asia; Food Security; Safety Nets; Food Bank; Ernährungssicherung; Ernährungspolitik; Südasien